Diagnóstico y evaluación del colector principal del sistema de alcantarillado combinado del municipio de Mistrató – Risaralda. - López Villada, Johan Andrés; Gutiérrez Orrego, Sebastián (Universidad Antonio Nariño, 2021)
For the population in general, it is of vital importance to have a basic sanitation service, which must be efficient, with the greatest possible coverage and offer good wastewater management for the benefit of the entire community. Under this concept, it is essential to implement sewerage systems, understood as a system for the collection, transport, treatment and final disposal of wastewater conducted through pipes generally located underground at depths determined according to design. In this document we will work on the evaluation of the infrastructure and the current operation of the main collector of the sewerage network of the municipality of Mistrató - Risaralda through the collection of information obtained from field visits and supply by the public utilities company.